"Alternative perspective in third world development:the case of Malaysia / edited by Masudul Alam Choudhury, Uzir Abdul Malik and Mohammad Anuar Adnan" - "Choudhury , Masudul" (London, 1996)
The Malaysian economy is developing fast within the context of increasing globalization. The book analyses in depth Malaysia's policies aimed at promoting international trade, economic growth and social welfare. It also studies Malaysia's position in the Southeast Asia region and in a global context. This analysis forms the basis for the formulation of an alternative development strategy, whose aim is producing a caring civil society and enhancing the general welfare of the population while developing the economy.
Keywords: Malaysia Economic policy